A Gene-Based Classification of Primary Adrenocortical Hyperplasias - Hannah-Shmouni, Fady; Stratakis, Constantine A. (Hormone and Metabolic Research, 2020)
Primary or adrenocorticotropin-independent adrenocortical tumors and hyperplasias represent a heterogeneous group of adrenocortical neoplasms that arise from various genetic defects, either in isolation or familial. The traditional classification as adenomas, hyperplasias, and carcinomas is non-specific. The recent identification of various germline and somatic genes in the development of primary adrenocortical hyperplasias has provided important new insights into the molecular pathogenesis of adrenal diseases. In this new era of personalized care and genetics, a gene-based classification that is more specific is required to assist in the understanding of their disease processes, hormonal functionality and signaling pathways. Additionally, a gene-based classification carries implications for treatment, genetic counseling and screening of asymptomatic family members. In this review, we discuss the genetics of benign adrenocorticotropin-independent adrenocortical hyperplasias, and propose a new gene-based classification system and diagnostic algorithm that may aid the clinician in prioritizing genetic testing, screening and counseling of affected, at risk individuals and their relatives.
Keywords: adrenal hyperplasia; Cushing syndrome; genetics; Carney complex; cyclic AMP; PPNAD; PMAH